2014
DOI: 10.1007/s00426-014-0608-y
|View full text |Cite
|
Sign up to set email alerts
|

Empirical validation of the diffusion model for recognition memory and a comparison of parameter-estimation methods

Abstract: The diffusion model introduced by Ratcliff (Psychol Rev 85:59–108, 1978) has been applied to many binary decision tasks including recognition memory. It describes dynamic evidence accumulation unfolding over time and models choice accuracy as well as response-time distributions. Various parameters describe aspects of decision quality and response bias. In three recognition-memory experiments, the validity of the model was tested experimentally and analyzed with three different programs: fast-dm, EZ, and DMAT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 69 publications
8
84
1
Order By: Relevance
“…On the one hand, Ratcliff (2002) and Wagenmakers, Ratcliff, Gomez, and McKoon (2008) used brightness discrimination and lexical discrimination tasks, respectively, to demonstrate both forms of validity in accumulation rate, starting point, and boundary separation parameters. However, in a recent study, Arnold, Bröder, and Bayen (2015) found evidence for convergent, but not discriminant validity of the Full Diffusion model parameters in the domain of recognition memory. For example, they found that their manipulation of response caution had a large effect on the boundary separation parameter, but also on the accumulation rate and non-decision time parameters.…”
Section: Threats To the Validity Of Cognitive Modelsmentioning
confidence: 90%
See 2 more Smart Citations
“…On the one hand, Ratcliff (2002) and Wagenmakers, Ratcliff, Gomez, and McKoon (2008) used brightness discrimination and lexical discrimination tasks, respectively, to demonstrate both forms of validity in accumulation rate, starting point, and boundary separation parameters. However, in a recent study, Arnold, Bröder, and Bayen (2015) found evidence for convergent, but not discriminant validity of the Full Diffusion model parameters in the domain of recognition memory. For example, they found that their manipulation of response caution had a large effect on the boundary separation parameter, but also on the accumulation rate and non-decision time parameters.…”
Section: Threats To the Validity Of Cognitive Modelsmentioning
confidence: 90%
“…For example, Arnold et al (2015) found that the EZ diffusion model, unlike the Full Diffusion model, showed both convergent and discriminant validity. Donkin, Brown, Heathcote, and Wagenmakers (2011) re-analyzed the lexical decision data set from Wagenmakers et al (2008) using both the Full Diffusion and LBA models.…”
Section: Threats To the Validity Of Cognitive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In any diffusion model study, the probably most important issue that a researcher has to examine is validity of parameters. In recent years, several experimental validation studies (e.g., Arnold, Bröder, & Bayen, 2015;Voss et al, 2004;Wagenmakers, Ratcliff, et al, 2008) and correlational analyses (e.g., Ratcliff, Thapar, & McKoon, 2011;Schubert, Hagemann, Voss, Schankin, & Bergmann, 2015) have supplied promising results regarding parameter validity. However, for any new paradigm, the validity has to be first examined.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental validation studies have been conducted supporting the validity of some or all of these four parameters using a color-discrimination task (Voss et al, 2004), a lexical-decision task (Wagenmakers, Ratcliff, Gomez, & McKoon, 2008), a motion discrimination task (Ratcliff & McKoon, 2008), brightness discrimination tasks (Ratcliff & Rouder, 1998) and-recently-also a recognition memory task (RMT; Arnold, Bröder, & Bayen, 2015). Furthermore, in correlational studies relationships between parameters and external criteria such as intelligence have been observed (e.g., Ratcliff et al, 2011).…”
Section: Psychological Interpretation Of the Diffusion Model Parametersmentioning
confidence: 99%